Danshenol A Alleviates Hypertension-Induced Cardiac Remodeling by Ameliorating Mitochondrial Dysfunction and Suppressing Reactive Oxygen Species Production. (11th September 2019) - Chen, Kai; Guan, Yiqing; Ma, Yunci; Quan, Dongling; Zhang, Jingru; Wu, Shaoyu; Liu, Xin; Lv, Lin; Zhang, Guohua
Abstract : Current therapeutic approaches have a limited effect on cardiac remodeling, which is characteristic of cardiac fibrosis and myocardial hypertrophy. In this study, we examined whether Danshenol A (DA), an active ingredient extracted from the traditional Chinese medicine Radix Salviae, can attenuate cardiac remodeling and clarified the underlying mechanisms. Using the spontaneously hypertensive rat (SHR) as a cardiac remodeling model, DA ameliorated blood pressure, cardiac injury, and myocardial collagen volume and improved cardiac function. Bioinformatics analysis revealed that DA might attenuate cardiac remodeling through modulating mitochondrial dysfunction and reactive oxygen species. DA repaired the structure/function of the mitochondria, alleviated oxidative stress in the myocardium, and restored apoptosis of cardiomyocytes induced by angiotensin II. Besides, DA inhibited mitochondrial redox signaling pathways in both the myocardium and cardiomyocytes. Thus, our study suggested that DA attenuates cardiac remodeling induced by hypertension through modulating mitochondrial dysfunction and reactive oxygen species.